THE EFFECTIVENESS OF SOCIAL MEDIA UTILIZATION AS A COLLABORATIVE TOOL IN HIGH SCHOOL MATHEMATICS LEARNING - Sarwoedi; Idi Warsah; Jumira Warlizasusi; Adisel (Jurnal Math-UMB.EDU, 2025)
This study examines the effectiveness of social media as a collaborative tool in high school mathematics learning. Social media enables students to collaborate, share materials, and engage in discussions flexibly. Using a qualitative descriptive approach, this study analyzes fiveteen accredited national and international journal articles as its research subjects, this research analyzes various social media platforms, including WhatsApp, Telegram, and Instagram, and their impact on student motivation, participation, and learning outcomes. The results indicate that social media enhances student collaboration, motivation, and understanding of mathematical concepts. However, challenges such as distractions, platform misuse, and low digital literacy among students persist. To address these issues, the study suggests strategies such as focused learning groups and digital literacy training for students and teachers. With proper management, social media can effectively improve the quality of mathematics learning in high schools.Keywords: Social media, collaboration, mathematics learning